Pengaruh Kebijakan Sistem Jaringan Transportasi Darat Melalui Type Kebijakan Push and Pull Policy dan Dampaknya terhadap Perekonomian Kota Makassar - Gafar, Muhammad Ikrar; Said, Lambang Basri; Maryam, St (Politeknik Negeri Ujung Pandang, 2019)
This study aims to analyze the effect of push and Pull policy (X) as an independent variable both partially and simultaneously on equitable economic development (Y1) and improve people's living standards (Y2) in Makassar City as the dependent variable. This research method uses a questionnaire with 50 respondents as a sample and has been selected from the population that has been selected based on sample criteria that have been determined. Sampling in this study are respondents which are chosen by researchers who reflect all stakeholders and elements of the community of Makassar City from various departments or fields of expertise, understanding and the problems related person. To measure variables, Likert Scale technique is used with scale weights from 1 to 5. To find out the correlation between variables X to Y, statistical techniques using Smart software PLS (Partial Least Square) is employed. The results of the study concluded that there was a significant positive effect of each independent variable on the dependent variable, namely the push and Pull policy (X) policy as an independent variable, partially or simultaneously influencing equal economic development (Y1) and improving people's living standards (Y2) in Makassar City.